HUBUNGAN INDEKS MASSA TUBUH TERHADAP KUALITAS TIDUR PADA LANJUT USIA DI DESA PENATIH - I.A. Pascha Paramurthi; I Made Dhita Prianthara; Kadek Liza Widya Astari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Background: The elderly population in recent years has experienced a significant increase. The condition and function of the body in the elderly are decreasing so that a person will experience a decrease in physical abilities which can affect body shape. Changes in body composition in the elderly include an increase in fat mass, a decrease in fat-free mass and a decrease in bone mass. These changes can increase and decrease the Body Mass Index (BMI). Sleep disturbance that affects sleep quality is sleep disordered breathing (SDB) and is closely related to a person's BMI level. The higher a person's BMI, the worse the quality of sleep, and vice versa. Purpose: This study aims to determine the relationship between obesity and sleep quality in the elderly. Methods: This study was a cross-sectional study. The sampling technique was simple random sampling. The research sample consisted of 49 elderly people. Results: Based on the chi-square test, the value of p = 0.043 (p